Development of Inorganic Solar Cells by Nano-technology - Zhang, Yafei; Geng, Huijuan; Zhou, Zhihua; Wu, Jiang; Wang, Zhiming; Zhang, Yaozhong; Li, Zhongli; Zhang, Liying; Yang, Zhi; Hwang, HueyLiang (Nano-Micro Letters, 2012)
Inorganic solar cells, as durable photovoltaic devices for harvesting electric energy from sun light, have received tremendous attention due to the fear of exhausting the earth’s energy resources and damaging the living environment due to greenhouse gases. Some recent developments in nanotechnology have opened up new avenues for more relevant inorganic solar cells produced by new photovoltaic conversion concepts and effective solar energy harvesting nanostructures. In this review, the multiple exciton generation effect solar cells, hot carrier solar cells, one dimensional material constructed asymmetrical schottky barrier arrays, noble nanoparticle induced plasmonic enhancement, and light trapping nanostructured semiconductor solar cells are highlighted.